PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS GAME TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DI SANGGAR BIMBINGAN MUHAMMADIYAH KAMPUNG BHARU MALAYSIA - Indah Nurcahyani Br Ginting; Ismail Saleh Nasution (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of game-based mathematics learning media on mathematical problem-solving abilities at the Muhammadiyah Kampung Bharu Malaysia Guidance Center. The population and sample of this study were grade 4 with 12 students as the experimental class. Data collection techniques in this study were observation, pretest and posttest tests and documentation. The research design in this study was One-Group Pretest-Postest. The results of the study obtained a t-test with a sig value of 0.000 with decision making if the sig value <0.05 then H1 is accepted and Ho is rejected. Thus, there is an Effect of Game-Based Mathematics Learning Media on Mathematical Problem-Solving Ability at the Muhammadiyah Kampung Bharu Malaysia Guidance Center.